Global Sensitivity Analysis Of In-Plane Elastic Buckling Of Steel Arches - Nguyen Τ. Η. (Engineering, Technology & Applied Science Research, 2020)
Steel arches are widely used in civil engineering and industrial structures. Their response depends on material properties, geometric dimensions, and boundary conditions. The objective of the current study is to perform global sensitivity analysis and to assess the influence of random input parameters on the in-plane elastic buckling of steel arches. The in-plane elastic buckling load of steel arches under uniform compression proposed in previous studies is adopted. The influence of the random input variables of the structure is evaluated using Sobol’s global sensitivity analysis. Monte Carlo simulation is also employed to rank the influence of input random variables.